Comparative study of labour progress and delivery outcome among induced versus spontaneous labour in nulliparous women using modified WHO partograph - Orji, Ernest O; Olabode, Taofeek O (Nepal Journal of Obstetrics and Gynaecology, 2008)
Aim: Induced or spontaneous labour has implication on the eventual mode of delivery and neonatal outcome. The objective of this study is to compare the progress and outcome of induced versus spontaneous labour among nulliparous women using the modified WHO partograph. Methods: Comparative study involving nulliparous women in active phase of labour with the cervix at least 4cm dilated. Those whose labours were induced were compared with those on spontaneous labour; both labouring women were monitored using modified WHO partograph. Outcome measures include the mean duration of labour, the eventual mode of delivery and the feto-material outcome. Data were managed using SPSS software. Chi-square t-test and student t-test were used in data analysis. Level of significance was placed at P < 0.05. Results: 136 women were compared in each group. There were no difference in mean age group, gestational age at delivery, cervical dilatation on admission, and the level of head of fifth palpable on admission. More women had spontaneous vaginal delivery among those in spontaneous labour (72.1% versus 64.7%) P=0.0001. There were less caesarean section among those in spontaneous labour (20.6% versus 35.3%). The mean Apgar scores were significantly better among induced labour babies (P=0.0001). While most induced labour cases reached or crossed action line compared to spontaneous labour (33.1% versus 16.9% P=0.002), there were more cases in spontaneous labour moving between alert and action line (27.9% versus 9.6%, P=0.000) Conclusion: Induced labour monitored with modified WHO partograph is comparative to spontaneous labour with no increased adverse feto maternal outcome. Key words: Induced versus spontaneous labour; modified WHO partograph, labour outcome.   doi:10.3126/njog.v3i1.1435 NJOG 2008 May-June; 3(1): 24 - 28